2015
DOI: 10.1007/s10666-015-9489-8
|View full text |Cite
|
Sign up to set email alerts
|

The Assessment of Road Traffic Air Pollution by Means of an Average Emission Parameter

Abstract: This work proposes a simple methodology to assess pollution loads discharged by road traffic within a specific temporal and spatial domain, in the case that detailed disaggregated data about vehicle fleet composition are not available at local scale. The adopted methodology starts by defining a useful specific emission function that allows easy calculation of the total amount of pollutant emissions in a year. The function, called yearly average vehicle (YAV), is representative of the annual average emission fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…in which EF j (g/kg) is the emission factor of the j-th pollutant [20], [21] ( Table 7). The results are reported in Table 8.…”
Section: Transportmentioning
confidence: 99%
“…in which EF j (g/kg) is the emission factor of the j-th pollutant [20], [21] ( Table 7). The results are reported in Table 8.…”
Section: Transportmentioning
confidence: 99%
“…Recordings (and the measurements of noxious emissions and of the noise level) were made over a period of two weeks, from November 6th, 2017 to November 24th, 2017 on every Monday, Wednesday and Friday during this period. Since the analysed speciality literature [4,5,6], indicated that it is also important to select appropriate time periods for the counting, the analyses were carried out both during the peak morning hours (from 07:30 a.m. to 8:30 a.m.) and during a "calmer" midday period, for reference (from 12:00 p.m. to 1:00 p.m.).…”
Section: The Analysed Area Means and Methodsmentioning
confidence: 99%
“…In order to single out the vehicle classes [14] for the studied case, the composition of the fleet running in the urban area pertaining to the Municipality of Reggio Calabria was taken into account [7]. Specifically, the studied fleet can be effectively classified by fuel type, so that two categories can be distinguished: gasoline or diesel fueled vehicles.…”
Section: Assessment Of the Pollutant Emissions Having A Local Impact mentioning
confidence: 99%